AL-DZHAWAHIR AL-'ARABIZIYAH : MUHAWALAH LI TA'ALUM AL-LUGHAH INFIRADIYAN MIN KHILAL AL-INTERNET - El-Zahraa, Fatima (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
This article analyzes the phenomenon of Arabizi ( عربي - إنجليزي ), using Arabic in Latin letters and numbers that mixed with dialects and foreign languages . This phenomenon is widespread in social media and can be used as one way to learn Arabic language independently with internet or social media. This paper is not intended to support the phenomenon, but rather as an alternative study to use of learning media more creatively. The results of this study indicate that Arabizi is an Arabic style that needs to be studied related to the contents and variety of language and Arab culture. DOI: 10.15408/a.v1i2.1146